EXOSC9 depletion attenuates P-body formation, stress resistance, and tumorigenicity of cancer cells - Yoshino, Seiko; Matsui, Yusuke; Fukui, Yuya; Seki, Masahide; Yamaguchi, Kiyoshi; Kanamori, Akane; Saitoh, Yurika; Shimamura, Teppei; Suzuki, Yutaka; Furukawa, Yoichi; Kaneko, Shuichi; Seiki, Motoharu; et al. (Scientific reports, 2020)
Cancer cells adapt to various stress conditions by optimizing gene expression profiles via transcriptional and translational regulation. However, whether and how EXOSC9, a component of the RNA exosome complex, regulates adaptation to stress conditions and tumorigenicity in cancer cells remain unclear. Here, we examined the effects of EXOSC9 depletion on cancer cell growth under various stress conditions. EXOSC9 depletion attenuated growth and survival under various stress conditions in cancer cells. Interestingly, this also decreased the number of P-bodies, which are messenger ribonucleoprotein particles (mRNPs) required for stress adaptation. Meanwhile, EXOSC2/EXOSC4 depletion also attenuated P-body formation and stress resistance with decreased EXOSC9 protein. EXOSC9-mediated stress resistance and P-body formation were found to depend on the intact RNA-binding motif of this protein. Further, RNA-seq analyses identified 343 EXOSC9-target genes, among which, APOBEC3G contributed to defects in stress resistance and P-body formation in MDA-MB-231 cells. Finally, EXOSC9 also promoted xenografted tumor growth of MDA-MB-231 cells in an intact RNA-binding motif-dependent manner. Database analyses further showed that higher EXOSC9 activity, estimated based on the expression of 343 target genes, was correlated with poorer prognosis in some cancer patients. Thus, drugs targeting activity of the RNA exosome complex or EXOSC9 might be useful for cancer treatment.